Компьютерная система обучения и контроля знаний студентов по дисциплине "Высшая математика" - Геворкян, Юрий Левонович; Чикина, Наталья Александровна (Национальный технический университет "Харьковский политехнический институт", 2010)
У статті показано автоматизовану систему навчання і контролю знань студентів, що розроблюється на кафедрі вищої математики Національного технічного університету „ХПІ ”. Наведено основні принципи її функціонування і можливі форми роботи з нею. Розглядається можливість використання системи в дистанційному навчанні.

In paper the automated system of training and the surveillance of knowledge of students is presented developed on chair of higher mathematics National technical university "KhPI". Main principles of its construction and possible operating modes in it are stated. Possibility of use of system as a tutorial to higher mathematics in remote courses is considered.
Сomputer system of training and the surveillance of knowledge of students on discipline "Higher mathematics"
Keywords: технические средства; вычислительная техника; дистанционная форма обучения; учебный процесс; НТУ "ХПИ"; интерактивные программы